Activity-Based Budgeting: Innovative Budgeting or an Efficiency Illusion? : A Systematic Literature Study - Sivano, Tamara Theresia; Sinta, Clara; Rizkiyah, Miftahul; Vanesca, Naqiyyah Ghina Kurnia; Sulbahari, Rifani Akbar (Peradaban Journal of Economic and Business, 2026)
This study evaluates the effectiveness of Activity-Based Budgeting (ABB) and Activity-Based Management (ABM) implementation to determine whether these systems constitute a strategic innovation or merely an illusion of efficiency. Employing a Systematic Literature Review (SLR) methodology in accordance with the PRISMA 2020 protocol, this research synthesizes 19 internationally reputable articles published between 2011 and 2025. The findings reveal a significant dialectic in global budgeting practices; while the majority of the literature positions ABB/ABM as a genuine innovation that enhances cost accuracy and resource transparency, the study also uncovers an "administrative illusion." In such cases, systems are often exploited for strategic behavioral manipulation or hindered by organizational cultural resistance. Additionally, neutral outcomes are observed in several contexts due to technical complexities and bureaucratic barriers. This study concludes that the transformation from traditional budgeting to activity-based systems requires robust institutional commitment and advanced data infrastructure to prevent the system from becoming a mere administrative formality. Theoretically, this research contributes to the contingency theory of management accounting, while practically, it provides a framework for organizations to assess their readiness for ABB/ABM adoption. Penelitian ini mengevaluasi efektivitas implementasi Activity-Based Budgeting (ABB) dan Activity-Based Management (ABM) untuk menentukan apakah sistem ini merupakan inovasi strategis atau sekadar ilusi efisiensi. Dengan menggunakan metode Systematic Literature Review (SLR) sesuai protokol PRISMA 2020, penelitian ini menyintesis 19 artikel bereputasi internasional yang diterbitkan antara tahun 2011 dan 2025. Temuan menunjukkan adanya dialektika yang signifikan dalam praktik penganggaran global; mayoritas literatur memosisikan ABB/ABM sebagai inovasi nyata yang meningkatkan akurasi biaya dan transparansi sumber daya. Namun, penelitian ini juga mengungkap adanya "ilusi administratif," di mana sistem dieksploitasi untuk manipulasi perilaku strategis atau terhambat oleh resistensi budaya organisasi. Selain itu, hasil netral ditemukan pada beberapa konteks akibat kompleksitas teknis dan hambatan birokrasi. Penelitian ini menyimpulkan bahwa transformasi dari penganggaran tradisional ke sistem berbasis aktivitas memerlukan komitmen institusional yang kuat dan infrastruktur data yang mumpuni agar tidak menjadi formalitas administratif semata. Secara teoretis, penelitian ini berkontribusi pada teori kontingensi akuntansi manajemen, sementara secara praktis, penelitian ini menyediakan kerangka kerja bagi organisasi untuk menilai kesiapan adopsi ABB/ABM.